Effect of drought environments on plant water relations and productivity of chickpea (Cicer arietinum) genotypes - Mathur, Khyati; Nanwal, R K; Pannu, R K (The Indian Journal of Agricultural Sciences, 2005)
A field experiment was conducted during 2002-04 winter season on sandy soil having low nitrogen, medium phosphorus and high potassium status at Hisar to study the effect of drought environments on plant water relations and productivity of chickpea genotypes. The experiment consisted of 3 environments of moisture (rainfed, terminal moisture stress and normal irrigated control) in main plots and 4 genotypes (’H 96-99’, ’H 99-270’, ’H 99-278’ and ’H 00-53’) in subplots of split-plot design having 3 replications. Results showed that the highest consumptive use and lowest water use efficiency were observed under normal irrigated control environment. Highest and lowest values of osmotic and turgor potential were recorded under normal irrigated control and rainfed environment, respectively. Under terminal moisture stress and normal irrigated control genotype ’H 99-270’ recorded highest yield. ’H 00-53’ out yielded (1028 and 1040 kg/ha during 2002- 03 and 2003-04, respectively) the other 3 genotypes under rainfed environment. ’H 99-270’ also recorded significantly highest biological yield.